Positive Identity Experiences of Young Bisexual and Other Nonmonosexual People: A Qualitative Inquiry. Issue 8 (3rd July 2017) - Flanders, Corey E.; Tarasoff, Lesley A.; Legge, Melissa Marie; Robinson, Margaret; Gos, Giselle
ABSTRACT: The majority of LGBTQ psychological research focuses on dysfunction. The exclusion of strengths-based perspectives in LGBTQ psychology limits the understanding of LGBTQ mental health. In this article we report experiences that young bisexual and other nonmonosexual people perceive as affirming of their sexual identity. A 28-day, daily diary study was used to investigate whether bisexual-identified participants encountered positive experiences related to their sexual identity, and which type of experiences they perceived to be positive. Using a constructivist grounded theory approach, participants' experiences were organized according to a social ecological model. Experiences were reported at the intrapersonal, interpersonal, and institutional levels, but most positive sexual identity experiences occurred at the interpersonal level. Implications for positive health outcome research and the integration of positive psychology with LGBTQ psychology are discussed, as well as study limitations.